Association between mental health self-care status and well-being-promoting behaviors among university students living in rural areas - Airi Endo; Sayuri Goryoda (PLoS ONE, 2025)
This study examined the relationship between the stages of behavioral changes related to mental health self-care and well-being (WB)-promoting behaviors. Students residing in a local city were invited to participate in an anonymous survey administered using Google Forms between Saturday, July 29, and Friday, August 4, 2023. The “Well-Being Promoting Behavior Inventory” was used to measure WB-promoting behaviors, and the respondents were asked to mark their responses. The scores for each of the four items were added (range, 32–160), and a Poisson regression analysis was conducted. The sum of these Well-Being promoting behavior scores was used as the dependent variable. The scores are non-negative integers and have the characteristics of count data. Since the variance was approximately equal to the mean, a Poisson regression model was deemed appropriate. The model’s assumptions, such as equivariance, were also evaluated and found to be reasonably satisfied. The stage of behavioral changes related to mental health self-care served as the explanatory variable, and the presence of worries or stress and sex were the adjustment variables. The mean age of the 113 subjects analyzed was 20.7 ± 1.42 years, with 51 men and 62 women. The distribution of behavioral change stages was 17.7%, 54.9%, 13.3%, 2.7%, and 11.5% in precontemplation, contemplation, preparation, action, and maintenance stages, respectively. Even after adjusting for the presence or absence of stress and sex, the proportion of those with more frequent WB-promoting behaviors was significantly higher in the “ Contemplation, Preparation, Action, and Maintenance” phase than in the “Precontemplation” phase (prevalence ratio [PR]=1.07, 95% confidence interval [CI]=1.02–1.13). Our results suggest an association between the behavior change stage in mental health self-care and WB-promoting behaviors. It may also be helpful to assist individuals in transitioning from the precontemplation stage to the contemplation stage when promoting behavioral changes related to mental health self-care, as significant differences were found after the contemplation stage. In the future, we believe that a larger sample size will be necessary for similar follow-up studies, to improve reliability and conduct a stratified analysis in a more detailed study.